PELAKSANAAN PENDEKATAN SCIENTIFIC PADA PEMBELAJARAN FISIKA DI SMA NEGERI DI KABUPATEN PIDIE - Nurfaizah Nurfaizah; Ahmad Farhan; Soewarno S (Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2017)
This study examines the problem of how the implementation of the scientific approach has been carried out in Physics learning in SMA Negeri Pidie district. The purpose of this research is to know how far the implementation of scientific approach in Physics subject in SMA Negeri in Pidie district. Subjects in this study were all physics teachers of SMAN applying Curriculum 2013 that is SMAN 1 Sigli, SMAN 2 Sigli, SMAN Unggul Sigli, SMAN 1 Mutiara, and SMAN 1 Sakti. While the Object is the plan of implementation of learning in the teacher and questionnaire implementation of scientific approach. The type of this research is qualitative research. Data collection in this research is done by method (1) questionnaire, and (2) documentation. The data were analyzed descriptive qualitative using percentage equation. The results showed that the implementation of the scientific approach in Physics learning in SMA Negeri in Pidie district has been running well. The average percentage of the implementation of the scientific approach of 77.85% means that teachers always take a scientific approach in the learning process.